2007
DOI: 10.4049/jimmunol.179.5.3362
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells in Perinatally HIV-1-Infected Children Exhibit Less Degranulation Compared to HIV-1-Exposed Uninfected Children and Their Expression of KIR2DL3, NKG2C, and NKp46 Correlates with Disease Severity

Abstract: NK cells play an integral role in the innate immune response by targeting virally infected and transformed cells with direct killing and providing help to adaptive responses through cytokine secretion. Whereas recent studies have focused on NK cells in HIV-1-infected adults, the role of NK cells in perinatally HIV-1-infected children is less studied. Using multiparametric flow cytometric analysis, we assessed the number, phenotype, and function of NK cell subsets in the peripheral blood of perinatally HIV-1-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 72 publications
5
60
0
2
Order By: Relevance
“…), we interpret that NK cells can contribute to both resistance against infection and to viral control once infected (Table 3). Together with data illustrating increased activation [10,20,91] and function [6,19] of NK cells in HESNs, these results suggest that NK cells fit the model of a candidate cell type whose retained function and heightened activation status may contribute to both control over HIV-1 replication and resistance to HIV-1 in HESN subjects.…”
Section: Nk Activity As a Correlate Of Resistance To Hiv-1 Infection mentioning
confidence: 54%
See 2 more Smart Citations
“…), we interpret that NK cells can contribute to both resistance against infection and to viral control once infected (Table 3). Together with data illustrating increased activation [10,20,91] and function [6,19] of NK cells in HESNs, these results suggest that NK cells fit the model of a candidate cell type whose retained function and heightened activation status may contribute to both control over HIV-1 replication and resistance to HIV-1 in HESN subjects.…”
Section: Nk Activity As a Correlate Of Resistance To Hiv-1 Infection mentioning
confidence: 54%
“…• Vertical transmission Children exposed to HIV-1 through carriage from HIV-1-infected mother HIV-1-specific T cell responses [11] Heightened innate immune cell activity [10,12] Oral exposure • Breastfeeding • Discordant couples (oral sex)…”
Section: Hiv-1-specific T Cell Responses In Hesn Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we have found that NKG2C and NKG2A expression is correlated to HIV viral load, similar to the findings of Ballan et al and Zeddou et al, respectively. 19,21 As only + / + individuals were used in our comparison, it can be suggested that HIV infection itself impacts the level of receptor expression. Therefore, the level of NKG2C and NKG2A expression will depend not only on a patient's genotype, but also on the extent of viremia.…”
Section: Nkg2c and Hivmentioning
confidence: 99%
“…In vivo analyses indicate that NK cells from patients with HIV-1 viremia are defective in target cell lysis compared to those from aviremic or uninfected control subjects (15,26). Disease severity in HIV-1 is associated with altered expression of different NK receptors and ligands, as shown by different studies (7,9,25,29,48). HIV-1 viral antigens have been shown to dysregulate NK cell function and its interaction with other accessory cells in the absence of direct infection through a multidirectional network of cytokines (26,27,39).…”
mentioning
confidence: 99%